Roles of mitochondrial benzodiazepine receptor in the heart - Sirirat Surinkaew (2018)
Mitochondrial benzodiazepine receptor (mBzR) is a type of peripheral benzodiazepine receptor that is located in the outer membrane of mitochondria. It is an 18-kDa protein that can form a multimeric complex with voltage-dependent anion channel (32 kDa) and adenine nucleotide translocator (30 kDa). mBzR is found in various species and abundantly distributed in peripheral tissues, including the cardiovascular system. The mitochondria are well known as the site of energy production, and the heart is the organ that highly requires this energy supply. In the past decades, it has been shown that mBzR plays a critical role in regulating mitochondrial and heart functions. A growing body of evidence demonstrates that mBzR is associated with regulation of mitochondrial respiration, mitochondrial membrane potential, apoptosis, and reactive oxygen species production. Moreover, mBzR has been suggested to play a role in alteration of physiological effects in the heart such as contractility and heart rate. mBzR is involved in the pathologic condition such as ischemia/reperfusion injury, responses to stress, and changes in electrophysiological properties and arrhythmogenesis. In this review, evidence of the roles of mBzR in the heart under both physiological and pathologic conditions is presented. Clinical studies regarding the use of pharmacologic intervention involving mBzR in the heart are also discussed as a possible target for the treatment of electrical and mechanical dysfunction in the heart. © 2011 Canadian Cardiovascular Society.